Perancangan Aplikasi Manajemen Pengelolaan Data Jemaat Berbasis Microservices Website - Septiadi, Michael; Purnamasari, Intan; Carudin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Data management that is still done manually at God’s DNA Cut Mutiah Church makes the data team have to do data collection manually as well. Hence, this makes the data team have to work extra by collecting new data needed directly. Errors such as inputting data incorrectly and the like may occur. This study aims to solve these problems by designing microservices-based data management application websites. Using the SDLC waterfall methodology can help facilitate the design of this application. The SDLC waterfall methodology has five stages: analysis, design, implementation, testing, and maintenance. In its implementation, to build microservices-based applications, this website is designed using MongoDB for databases, ReactJS at the front, and FastAPI Python at the back. This application has been tested using the white-box testing method, and the results of the test run according to the design and needs determined.